Program Sahabat Obat Sebagai Upaya Pengendalian Hipertensi di Desa Purwosari Kecamatan Babadan - Kholifatul Ibra Tyra Zahrani; Bian Shabri Putri Irwanto (SEHATI: Jurnal Kesehatan, 2026)
Hypertension is one of the leading causes of mortality worldwide and remains a major public health problem. Based on the 2024 Health Profile of Puskesmas Babadan, hypertension was the most prevalent non-communicable disease, with 263 recorded patients, indicating the need for community-based interventions to improve hypertension management. The Sahabat Obat Program was an innovative initiative conducted by the Faculty of Public Health, Universitas Airlangga, in 2025 to support hypertension control in Purwosari Village. The program aimed to increase medication adherence among hypertension patients and improve knowledge of hypertension management among pre-elderly and elderly individuals. Implementation involved situational analysis using the PRECEDE–PROCEED model, problem prioritization using the USG method, problem analysis using a fishbone diagram, and selection of alternative solutions using the MEER approach. The program was conducted in January 2025 at the Purwosari Village Hall, involving 50 pre-elderly and elderly hypertension patients and 31 family members as Medication Taking Companions (PMOs). The findings showed an increase in participants’ knowledge regarding adherence to antihypertensive medication. In conclusion, the Sahabat Obat Program positively contributed to improving medication adherence, and community members are encouraged to maintain adherence, strengthen family support, adopt healthy lifestyles, and routinely monitor blood pressure to support sustainable hypertension control.